Kajian Pertanggung jawaban Pidana Seorang Notaris Dalam Pembuatan Akta Otentik Yang Didasarkan Pada Keterangan Palsu: Studi Putusan Nomor: 773/Pid.B/2021/Pn Smg - Zalfa Kamelia Rona Afsila (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study aims to determine the criminal liability of a Notary who makes an authentic deed based on false information in the Semarang District Court decision Number 773/Pid.B/2021/PN Smg and knows the legal consequences of an authentic deed based on false information. This research uses normative legal research methods or can be called literature law research. This study examines a rule of law, legal principles, and legal doctrines associated with Semarang District Court Decision Number 773/Pid.B/2021/PN Smg to answer the legal issues faced. The types of legal materials used include primary legal materials and secondary legal materials. Meanwhile, the technique of collecting legal materials uses literature study techniques by collecting and reviewing the contents of legal materials in the form of books, laws and regulations, legal journals, legal articles, and previous research related to the problems to be researched and the data analysis techniques used are qualitative data analysis with document analysis methods, namely reviewing the Semarang District Court Decision Number 773 / Pid.B / 2021 / PN Smg with reference to the legislation relevant. The results showed that the Panel of Judges based on Semarang District Court Decision Number 773/Pid.B/2021/PN Smg in imposing criminal sanctions against Notaries who commit the crime of forgery of authentic deeds is based on the Criminal Code (KUHP). This is because the Notary Office Law (UUJN) is not specifically regulated regarding criminal sanctions. The legal consequence of an authentic deed based on false information is that it does not automatically become null and void. The annulment of an authentic deed becomes the authority of the civil judge. The mechanism for cancellation of a deed is by a party who submits a lawsuit for cancellation to the court